PHYSICAL EXAMINATION IN AESTHETICS: BODY ASSESSMENT PROTOCOLS FOR OPTIMIZING RESULTS AND THERAPEUTIC SAFETY (CIPEEX, 2025)
Physical examination and body assessment are essential procedures in aesthetics, as they allow for the analysis of parameters related to body composition and aesthetic alterations such as lipodystrophy, sagging skin, and cellulite. The objective of this study was to reinforce the importance of systematic assessment to ensure greater accuracy and safety during interventions, consolidating a personalized and effective approach. To this end, a narrative review of national and international scientific literature was conducted in the PubMed, SciELO, and LILACS databases. The study included anthropometric assessment methods, postural analysis, inspection, palpation, and non-invasive technologies such as bioimpedance. The review demonstrated that systematic body assessment allows for the identification of fat distribution, muscle tone, and body symmetry, as well as aesthetic dysfunctions and possible contraindications. This information is crucial for developing personalized treatment plans, optimizing safety and promoting superior clinical results. The use of non-invasive technologies complements manual assessment by providing accurate quantitative data. In conclusion, body assessment is an indispensable resource for understanding the body's current condition, guiding treatment, and monitoring the progress of results. Its systematic application consolidates evidence-based practice, raises the standard of care, and strengthens the relationship of trust between professional and patient.